1993
DOI: 10.1002/maco.19930440306
|View full text |Cite
|
Sign up to set email alerts
|

Metal dusting of high temperature alloys

Abstract: Metal dusting, i.e. disintegration into fine metal particles and carbon, was induced on a selection of chromia forming high temperature alloys in a flowing CO-H2-H20 atmosphere in exposures at 650°C, 600"C, 5004 and 450°C. The materials were pretreated by annealing in Hz at 1000 "C and electropolishing, this leads to large grain size and low surface deformation, both is disadvantageous for formation of a Crz03 scale. The resistance to metal dusting is only dependent on the ability to form a protective Crz03 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 8 publications
(4 reference statements)
2
76
0
1
Order By: Relevance
“…In addition to low-alloy steels reported widely so far, [1][2][3][4][5][6] experience with metal dusting of high-alloy steels, originally resistant to carburization, has been reported in actual plants as well. [7][8][9][10][11] Moreover, laboratory corrosion tests for development of eminent alloys required for severe metal dusting attack have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to low-alloy steels reported widely so far, [1][2][3][4][5][6] experience with metal dusting of high-alloy steels, originally resistant to carburization, has been reported in actual plants as well. [7][8][9][10][11] Moreover, laboratory corrosion tests for development of eminent alloys required for severe metal dusting attack have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Ni-base alloys possess better resistance against metal dusting attack than the Fe-base alloys (Grabke et al 1993, Maimer and Norton 1999. The reason has not been clear thus far.…”
Section: Objectivesmentioning
confidence: 98%
“…It was suggested that an oxide scale protects alloys, and metal dusting corrosion starts at defects in the oxide scale (Grabke 1998, Grabke et al 1993, 1998. Carbon penetrates through the defects and undermines the oxide scale.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the important step in the metal dusting for carbon steels is the formation of an unstable cementite (Fe 3 C) as an intermediate followed by its decomposition. [2] On the other hand, the alloys which demonstrate high corrosion resistance in high-temperature oxidization atmosphere by containing high Cr. Although the protective oxide layer forms on these alloys in that environment, carbon, beyond the limit of solid solution, goes through the defective part of that oxide layer on the alloy surface as graphite while in use.…”
Section: Introductionmentioning
confidence: 99%